1994
DOI: 10.1007/bf00577738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ethanol sclerotherapy and emptying with injection of saline in treatment of thyroid cysts

Abstract: We compared the results of ethanol sclerotherapy in thyroid cysts with emptying of cysts and instillation of saline. Twenty-six patients with recurrent thyroid cysts were treated with cyst aspiration and subsequent ethanol sclerotherapy. A control group of 44 patients was submitted to cyst aspiration and subsequent injection with isotonic saline; among them 20 had previously been treated with repeated aspirations of the cyst fluid. The patients were followed up clinically and ultrasonically 1 and 12 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 13 publications
1
24
1
5
Order By: Relevance
“…In different studies, the pain was reported in 2.5% to 30% or, in large cysts, even 70% of patients 14,18,21 . Occasionally, temporary vocal fold paralysis and dysphonia or, rarely, transient thyrotoxicosis may occur 22 . In the largest set of 432 complex cysts, Lee and Ahn reported transient localized pain in 32 (7.9%) and temporary vocal fold paralysis in only 3 (0.7%) patients 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, the pain was reported in 2.5% to 30% or, in large cysts, even 70% of patients 14,18,21 . Occasionally, temporary vocal fold paralysis and dysphonia or, rarely, transient thyrotoxicosis may occur 22 . In the largest set of 432 complex cysts, Lee and Ahn reported transient localized pain in 32 (7.9%) and temporary vocal fold paralysis in only 3 (0.7%) patients 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the surgical removal of benign cystic thyroid nodules, several therapeutic methods, such as percutaneous simple aspiration, thyroid hormone suppression therapy, percutaneous tetracycline instillation, or US-guided PEI, have been utilized (14,15). At present, a US-guided PEI has become the first line treatment method for benign cystic or solid thyroid nodules because of its ease and safety (1 8).…”
Section: Discussionmentioning
confidence: 99%
“…Cistos com diâmetro maior que 4cm ou aspirados hemorrágicos apresentariam maior probabilidade de recorrência (9,10 A mediana de 4 injeções utilizadas nos nossos pacientes com nódulos císticos é maior que de outros trabalhos da literatura, que utilizaram 1 a 2 injeções para tratamento de cistos puros (9,11,30). Este fato deve-se ao número maior de cistos com componente sólido em nossa casuística, o que nos obrigou a um número maior de sessões para a redução do componente sólido dos mesmos.…”
Section: Discussionunclassified
“…Este fato deve-se ao número maior de cistos com componente sólido em nossa casuística, o que nos obrigou a um número maior de sessões para a redução do componente sólido dos mesmos. Contudo, a inclusão dos nódulos mistos não interferiu na percentagem de redução final dos nódulos (92%), quando comparada a outras séries que obtiveram redução entre 72 e 95% (9,11,12,30).…”
Section: Discussionunclassified
See 1 more Smart Citation